Optimization of Solvent Type on Antioxidant Activity of Spirulina platensis Extract and Its Pharmaceutical Tablet Formulation - Bagiana, I Kadek; Franyoto, Yuvianti; Mutmainah; Kusmita, Lia (Tropical Biopharmaca Research Center, IPB University, 2025)
Spirulina platensis contains nutrients such as proteins, essential amino acids, fatty acids, minerals, pigments, carotenoids, and vitamins, which have strong antioxidant properties. This study evaluated the impact of extraction solvents (70% methanol, 70% ethanol, and 70% acetone) on antioxidant activity, with the most effective extract formulated into tablets. Extraction was performed by maceration. Tablet preparations were characterized by moisture content, flow rate, angle of repose, organoleptic properties, weight uniformity, hardness, disintegration time, and friability. The results showed that the 70% methanol extract exhibited the highest antioxidant activity (IC₅₀ = 45.57 ± 0.01 ppm), superior to 70% acetone (IC₅₀ = 67.15 ± 0.07 ppm) and 70% ethanol (IC₅₀ = 85.32 ± 1.21 ppm), although lower than vitamin C (IC₅₀ = 3.52 ± 0.01 ppm). Tablets prepared from 70% methanol extract fulfilled all pharmaceutical quality requirements.